Molecular Identification of Campylobacter jejuni and Campylobacter coli Isolated from Small-Scale Poultry Slaughterhouse in Lima, Peru - Lazaro , Cesar A.; Conte-Junior, Carlos A.; Vilca, Miguel A.; Lucas, Juan R.; Ramos, Daphne D.; Manchego, Alberto; Chiok, Kim R.L.; Franco, Robson M. (International Journal of Poultry Science, 2012)
A total of 96 samples (3 scalding water, 3 final washing water, 30 non-eviscerated, 30 eviscerated and 30 cecal content) from three small-scale broiler slaughterhouses were evaluated. Bacteriological test was performed with mCCDA medium and positive samples were confirmed by PCR assays using 16S rDNA, hipO and asp primers to Campylobacter spp., Campylobacter jejuni and Campylobacter coli respectively. Bacteriological test showed the presence of Campylobacter spp. in 60 samples. However, according to the PCR assays, only 19 samples were confirmed as positive. Non-eviscerated and eviscerated carcasses had fewer numbers of samples positive for Campylobacter spp. (63 and 50%, respectively) than the cecal content samples (77%). No positive were found in the scalding and the final washing water samples. No differences (P>0.05) were observed between PCR and biochemical tests for Campylobacter jejuni and Campylobacter coli identification. Chicken meats from small-scale slaughterhouses in Lima, Peru are potential reservoirs of Campylobacter jejuni and Campylobacter coli and this contamination was associated to some deficiencies in slaughter process, principally during the evisceration process. The method presented in this paper has shown to be suitable determination of Campylobacter species in faecal, meat and water samples.